3D printed geometrically tessellated sheets with origami-inspired patterns. (March 2022) - Wickeler, Anastasia L.; Naguib, Hani E.
This study demonstrates that the impact energy absorption capabilities of flexible sheets can be significantly enhanced by implementing tessellated designs into their structure. Configurations of three tessellated geometries were tested; they included a triangular-based, a rectangular-based, and a novel square-based pattern. Due to their geometrical complexity, multiple configurations of these tessellations were printed from a rubber-like material using an inkjet printer with two different thicknesses (2 and 4 mm), and their ability to absorb impact energy was compared to an unpatterned inkjet-printed sheet. In addition, the effect of multi-sheets stacking was also tested. Due to the tailored structure, the impact testing showed that the single-layer sheets were more effective at absorbing impact loads, and experience less deformation, than their two-layer counterparts. The 4 mm thick tessellated patterns were most effective at absorbing impact loads; all three thick patterns measured about 40% lower impact forces transferred to the base of the samples compared to the unpatterned counterparts.